2004
DOI: 10.1111/j.1365-313x.2004.02196.x
|View full text |Cite
|
Sign up to set email alerts
|

AtSUC8 and AtSUC9 encode functional sucrose transporters, but the closely related AtSUC6 and AtSUC7 genes encode aberrant proteins in different Arabidopsis ecotypes

Abstract: SummaryThree members of the Arabidopsis sucrose transporter gene family, AtSUC6-AtSUC8 (At5g43610; At1g66570; At2g14670), share a high degree of sequence homology in their coding regions and even in their introns and in their 5¢-and 3¢-flanking regions. A fourth sucrose transporter gene, AtSUC9 (At5g06170), which is on the same branch of the AtSUC-phylogenetic tree, shows only slightly less sequence homology. Here we present data demonstrating that two genes from this subgroup, AtSUC6 and AtSUC7, encode aberra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
100
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 50 publications
4
100
0
Order By: Relevance
“…In the Arabidopsis genome, there are nine annotated Suc transporter genes (Sauer, 2007). However, SUC2 is the only Suc transporter that is specifically involved in phloem loading of Suc from leaf mesophyll cells (Sauer et al, 2004). It has been shown that the disruption of SUC2 function led to high accumulation of Suc in leaves and blocked Suc transport from leaves to root tissues (Gottwald et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Arabidopsis genome, there are nine annotated Suc transporter genes (Sauer, 2007). However, SUC2 is the only Suc transporter that is specifically involved in phloem loading of Suc from leaf mesophyll cells (Sauer et al, 2004). It has been shown that the disruption of SUC2 function led to high accumulation of Suc in leaves and blocked Suc transport from leaves to root tissues (Gottwald et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, SUC1 is mainly expressed in floral tissue and developing seeds, whereas SUC5 expression is embryo specific. In the same subgroup as SUC2, SUC6 and SUC7 are annotated as pseudogenes, and SUC8 and SUC9 are expressed in floral tissues (Sauer et al, 2004). SUC3 and SUC4 belong to two different subgroups.…”
Section: The Hps1 Mutation Affects Plant Root Developmentmentioning
confidence: 99%
“…SUC5 could also act at the interface between the endosperm and embryo, since it is expressed in the endosperm and specifically the epidermis of the outer surface of the cotyledons (Supplemental Figure 7B) (Pommerrenig et al, 2013). Data from a SUC9 translational fusion to GUS indicated that SUC9 protein was also present in the embryo (Sivitz et al, 2007), although no transcriptional GUS activity was detected in seeds (Sauer et al, 2004). All these reports are in agreement with the observation that in vitro dissected embryos from the globular stage can reach the mature stage when grown in media supplemented with sucrose.…”
Section: Functional Model Of Sweets In Sucrose Translocation In Seedsmentioning
confidence: 99%
“…Long-distance and intercellular transport of sugars is mediated by protoncoupled Suc transporters (belonging to the disaccharide transporter family) and hexose and polyol transporters (belonging to the monosaccharide transporter family). Many of these transporters have been identified in a wide range of species (Lemoine, 2000;Sauer et al, 2004;Bü ttner, 2007). Disaccharide transporter genes belong to small multigenic families (e.g.…”
mentioning
confidence: 99%
“…Disaccharide transporter genes belong to small multigenic families (e.g. nine members in Arabidopsis [Arabidopsis thaliana] and four in tomato [Solanum lycopersicum]; Sauer et al, 2004;Hackel et al, 2006) and can be clustered into four groups regarding the homologies of the encoded protein sequences. The Arabidopsis genome has 53 homologous sequences encoding putative monosaccharide transporters, which are distributed into seven distinct clusters (Bü ttner, 2007).…”
mentioning
confidence: 99%